Effects of Ar/H2 annealing on the microstructure and magnetic properties of CoO nanoparticles. Issue 86 (18th September 2015) - He, Xuemin; Li, Zhiwen; Zhang, Xing; Qiao, Wen; Song, Xueyin; Yan, Shiming; Zhong, Wei; Du, Youwei
<x xml:space="preserve">Abstract</x> Hysteresis loops and ZFC/FC curves of the Co/CoO composite nanoparticles.